Xhosa twins as a theme in conceptually motivated sculptural artworks - Ngcai, Sonwabiso (My University, 2015)
My Masters of Fine Arts degree consists of two components: the dissertation and practical works in the form of sculptures displayed as an exhibition. This body of work explores myth, belief and ritual practices relating to birth, life and death of twins in Xhosa culture. The purpose of the dissertation is to enrich and reflect on both the understanding of Xhosa ritual practices and that of my own work. The study will hopefully add significantly to the body of knowledge about Xhosa Indigenous Knowledge Systems as relating to twins. UNESCO emphasizes that Indigenous Knowledge Systems are part of immaterial cultural heritage such as languages, music and dance, festivities, rituals and traditional craftsmanship, and this cultural heritage is important for the identity of a society (Kaya & Masoga 2008:2). The choice of employing autoethnography in this qualitative study is derived from lived experience. Born as a twin in a rural Xhosa community, I experienced some unusual practices during my upbringing and thus a qualitative research method is used, involving auto-ethnography. This methodological approach aims at exploration of personal experience as a focus of investigation. The study also looks briefly at Yoruba twins as a means of finding similarities and commonalties with those of Xhosa culture.
M. Tech. (Fine Art, Department of Visual Arts and Design, Faculty of Human Sciences), Vaal University of Technology|
Keywords: Twins in Xhosa culture; Indigenous knowledge systems; Auto-ethnography; Yoruba twins; 730.968; Sculpture, African.; Xhosa (African people); Twins in art